Cognitive remediation therapy (CRT) in a specialist inpatient eating disorder service for children and adolescents: CAN‐CRT study protocol for a pilot randomised controlled trial. (26th March 2018) - Giombini, Lucia; Nesbitt, Sophie; Cox, Hannah; Foxall, Anna; Sharia, Teo; Easter, Abigail; Tchanturia, Kate
Abstract: Introduction: Research on treatments for young people (YP) with anorexia nervosa (AN) is scarce. Evidence supports the use of cognitive remediation therapy (CRT) to improve central coherence and set‐shifting, inefficiencies that can negatively impact on prognosis. Objective: The study aims to evaluate the feasibility of individual CRT in an inpatient setting for YP aged 10–18 years with AN and to qualitatively examine YP's and their parents experiences. Method: In a single‐centre, pilot, randomised controlled trial, 80 patients aged 10–18 years with AN will be randomly allocated to the immediate or delayed CRT group, in addition to standard treatment. A repeated measures design will be conducted across 3 time points. Discussion: The data will provide evidence regarding the feasibility of individual CRT in YP with AN, informing directions of further development of CRT. The study is in preparation for a definitive randomised controlled trial. The aim of this manuscript is to describe the study protocol.